2008
DOI: 10.1136/bmj.39471.430451.be
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acupuncture on rates of pregnancy and live birth among women undergoing in vitro fertilisation: systematic review and meta-analysis

Abstract: Objective To evaluate whether acupuncture improves rates of pregnancy and live birth when used as an adjuvant treatment to embryo transfer in women undergoing in vitro fertilisation. Design Systematic review and meta-analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
98
2
8

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(112 citation statements)
references
References 44 publications
3
98
2
8
Order By: Relevance
“…24 Conversely, other meta-analyses have suggested that acupuncture given with embryo transfer improves rates of pregnancy and live birth among women undergoing IVF. 25 In another systematic review, Cheong et al 26 suggested that acupuncture performed on the day of embryo transfer has a benefi cial effect on the live birth rate; however, with the present evidence this could be attributed to placebo effect.…”
Section: Introductioncontrasting
confidence: 54%
See 1 more Smart Citation
“…24 Conversely, other meta-analyses have suggested that acupuncture given with embryo transfer improves rates of pregnancy and live birth among women undergoing IVF. 25 In another systematic review, Cheong et al 26 suggested that acupuncture performed on the day of embryo transfer has a benefi cial effect on the live birth rate; however, with the present evidence this could be attributed to placebo effect.…”
Section: Introductioncontrasting
confidence: 54%
“…28 A recent meta-analysis evaluated the effects of acupuncture on IVF clinical outcomes and concluded that acupuncture on the embryo transfer day may improve both pregnancy and live birth rates. 25 In addition, three prospective randomised published studies recorded higher pregnancy rates in the acupuncture group than in the control group. 22 23 27 This study evaluated the effect of 25 min acupuncture sessions immediately before and immediately after embryo transfer in 208 patients undergoing ICSI cycles and no benefi t of acupuncture was observed in the clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of uterine contractions might be another potential mechanism for reduction of miscarriage rates found in our study. In a systematic online review and meta-analysis of seven trials involving 1366 women undergoing IVF and IVF in conjunction with acupuncture treatments on day of embryo transfer [18] an increase in clinical pregnancy (odds ratio 1.65, 95% confidence interval 1.27 to 2.14; number needed to treat (NNT) 10 (7 to 17); seven trials), ongoing pregnancy (1.87, 1.40 to 2.49; NNT 9 (6 to 15); five trials), and live birth (1.91, 1.39 to 2.64; NNT 9 (6 to 17); four trials) was reported. While the miscarriage rates were not specified, live birth rates were determined to be higher in the acupuncture group.…”
Section: Discussionmentioning
confidence: 99%
“…Dentre essas alternativas, a literatura científi-ca mostra que a acupuntura pode melhorar significativamente a taxa de nascidos vivos, sugerindo que a técnica aumenta as chances de gravidez clí-nica em 65% dos casos comparados com o grupo controle 16 . Entretanto, não são todos os trabalhos científicos que apresentam eficácia relacionando acupuntura e fertilização.…”
Section: Acupuntura Na Infertilidade Feminina E Processo De Fertilizaçãounclassified